Cover Picture: Graphane Nanostripes (Angew. Chem. Int. Ed. 45/2016). Issue 45 (26th September 2016) - Wang, Lu; Sofer, Zdeněk; Bouša, Daniel; Sedmidubský, David; Huber, Štěpán; Matějková, Stanislava; Michalcová, Alena; Pumera, Martin
Abstract : The interplay of metallic nanoparticles and defects in hydrogenated carbon nanostripes leads to spin polarization and induction of a ferrogmagnetic moment. In their Communication onpage 13965 ff., M. Pumera et al. show that the presence of metallic nanoparticles incorporated into graphane nanostripes has a positive effect on electrocatalytic properties towards the hydrogen evolution reaction.